DAMPAK LIBERALISASI EKONOMI TERHADAP HUKUM PERTANAHAN DI INDONESIA - Herry, Musleh (Fakultas Syariah, 2009)
The developmental program of the government creates delicate issues concerning the proper allocation of land. While the government program of welfare necessitates the availability of land to build housings, roads, factories and business centers, the plight of society displaced from their land should not be overlooked. Liberalist approach on managing land proves to bring more problem than solution to the society at large. Through the strong capital and wide network in executive and legislative bodies, the liberalist proponents manage to seize huge amounts of land at the expense of the original owners, mostly villagers who lack of apprehension about the price of land. The vague regulation concerning land also contributes to the handover of huge acres of land from the villagers to the capital owners. Without government intervention on the land market, it is worried that the process of land acquisition by the capital owner will run out of control.Program pembangunan pemerintah memunculkan masalah seputar penguasaan tanah. Sementara di sisi lain program pemerintah untuk kesejahteraan membutuhkan ketersediaan tanah untuk membangun perumahan, jalan, pabrik pusat -pusat bisnis. Persoalan berat kepemilikan tanah yang dihadapi masyarakat harus mendapat perhatian.PendekatanÂ kelompok liberal terhadap pengaturan penguasaan tanah menimbulkan banyak persoalan bagi masyarakat secara luas. dengan menggunakan modal yang besar danÂ jaringan yang kuat di lembaga eksekutif dan legislatif, pendukung kelompok liberal mengambil alih kepemilikan tanah secara besar-besaran terutama dari penduduk desa yang tidak mengetahui harga tanah yang semestinya. Peraturan yang masih belum jelas berkaitan dengan tanah juga menyebabkan pindah kepemilikan dari petani ke pemilik modal. Tanpa intervensi dan kontrol dari pemerintah terhadap pemasaran tanah, dikhawatirkan persoalan penguasaan tanah oleh pemilik modal akan lepas kontrol.Keywords: Liberalisasi Ekonomi, Penguasaan Tanah, Hak Milik